The Association Between Serum Gamma‐Glutamyl Transferase and Gastrointestinal Cancer Risk: A Systematic Review and Meta‐Analysis - Alireza Ramandi; Jacob George; Amir Hossein Behnoush; Alireza Delavari; Zahra Mohammadi; Hossein Poustchi; Reza Malekzadeh (Cancer Medicine)
ABSTRACT Background Gamma‐glutamyl transferase (GGT) has been shown to have associations with several diseases including cancers. Previous studies have investigated the effect of GGT levels on the gastrointestinal (GI) cancer incidence. We aim to systematically investigate these studies to provide better insights into the interrelationship between GGT and GI cancers. Methods Online databases were searched to find relevant studies investigating different GGT levels' effects on the incidence of GI cancers including colorectal, esophageal, liver, pancreas, gastric, and biliary duct cancers. Random‐effect meta‐analysis was conducted to pool the hazard ratios (HRs) of GGT quartiles (Qs) effect on cancer incidence. Results A total of 26 studies were included in the final review, 12 of which underwent meta‐analysis that investigated 11 million patients. Based on the meta‐analysis, Q4 patients had a 69% higher hazard of GI cancer incidence (HR 1.69, 95% CI 1.41–2.02, p‐value < 0.001). The hazard ratio significance was also similar for Q3 (HR 1.22, 95% CI 1.15–1.30, p‐value < 0.001) and Q2 (HR 1.10, 95% CI 1.05–1.16, p‐value =0.002) of GGT. Colorectal and liver cancers showed a higher hazard ratio among Q2, Q3, and Q4 of GGT compared to Q1. In pancreas and bile duct cancers, only Q4 of GGT had significantly higher HR. Q3 and Q4 of GGT levels had statistically significant associations with gastric cancer incidence. Conclusion Higher GGT levels correlate with higher rates of GI cancer incidence, especially in colorectal and hepatic cancers. Future studies should investigate this biomarker's potential role in risk assessment for digestive cancers.